2010
DOI: 10.2979/mew.2010.6.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Between Fashion and Tesettür

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Indiana University Press is collaborating with JSTOR to digitize, preserve and extend access to Journal of Middle East Women's Studies. ABSTRACTSince the 1980s, fashionable Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(6 citation statements)
references
References 27 publications
2
3
0
1
Order By: Relevance
“…Our findings support El-Bassiouny (2018), who found that the hijab has become a tradition blended with modernity. Our study validates the previous studies (Moors, 2007;Mulali, 2009;Gökariksel and Secor, 2010;Almila, 2016;El-Bassiouny, 2018), which found that Muslim women engage in mediation between veiling and fashion. In our study, participants emphasized that the hijab can be eye-catching but should also represent modesty.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support El-Bassiouny (2018), who found that the hijab has become a tradition blended with modernity. Our study validates the previous studies (Moors, 2007;Mulali, 2009;Gökariksel and Secor, 2010;Almila, 2016;El-Bassiouny, 2018), which found that Muslim women engage in mediation between veiling and fashion. In our study, participants emphasized that the hijab can be eye-catching but should also represent modesty.…”
Section: Discussionsupporting
confidence: 92%
“…Some even wore Dian Pelangi's designer pieces which might be priced more than IDR 1 million or SGD 100. In line with the results of research conducted by Gökarıksel & Secor, (2010) ;Jones, (2007) explains that the function of clothing is to increase value. Muslim fashion and clothing are two opposites, but in reality, women can change the concept and brand them as a 'new way.'…”
Section: Majelis Taklim As a Tool For Hijrahsupporting
confidence: 68%
“…Middle-class Muslims in Surabaya are interesting to study because the middle class can be a hub for the construction of identity as philanthropy in society. The Muslim middle class was founded on the principle of al-maslah ah al-ammah (Gökarıksel & Secor, 2010;Jones, 2007). An interesting study revealed that there were women or mothers than men or fathers as member Majelis Taklim which was strengthened by data collected from the Ministry of Religion in 2019: Therefore, Majelis Taklim is often associated with women.…”
Section: Introductionmentioning
confidence: 99%
“…The Islamist movement caused a dramatic change in some urban women's clothing, as increasing numbers began to wear headscarves. In parallel with the process of economic liberalization and the emergence of devout Muslim male entrepreneurs, a market for urban Islamic attire developed (Gökarıksel and Secor 2010;Sandıkçı and Ger 2002). Although not all urban female veiling practitioners supported Islamist politics, the Islamist Welfare Party's (RP) success in the 1994 local elections and RP's becoming a partner in a coalition government in 1996 came as a shock to secular sections of society (Çınar 2005).…”
Section: The Politics Of (Un)veiling In Turkeymentioning
confidence: 99%